129I in a sediment core offshore Fukushima: Distribution, source and its implication. (August 2020) - Fan, Yukun; Hou, Xiaolin; Fukuda, Miho; Zheng, Jian; Aono, Tatsuo; Chen, Ning; Zhang, Luyuan; Zhou, Weijian
Abstract: 129 I released from the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident has been observed in the atmospheric, terrestrial and oceanic environments, and it also entered the marine sediments via dispersion by sea water movement and deposition around Japan. However, there have been few studies of marine sediment cores in contrast to the large number of studies on seawater. In this work, a sediment core collected near FDNPP was analyzed for 129 I. It is observed that the 129 I/ 127 I atomic ratios in this sediment core are comparable to those in the seawater and sediments collected from offshore Fukushima after the accident, but 2 orders of magnitude higher than those in seawater in this region before the accident, suggesting the significant amount of 129 I has been transferred and incorporated to the offshore shallow sediments. The difference in environmental behavior between 129 I and 137 Cs is discussed based on their depth distributions in the sediment core in comparison with the grain size distribution of sediments. The peak concentrations of iodine isotopes were found in a relatively deeper layer than radiocesium. Radiocesium follows the distribution of fine grains in the sediment core, implying its high association to fine grains. Graphical abstract: Image 1 Highlights: Fukushima accident caused elevated 129 I/ 127 I ratio up to 10 −9 in offshore sediment. 129 I/ 137 Cs activity ratios were found to be higher than the Fukushima effluent. 129 I peaks in a deeper layer than 137 Cs does. Cs was concentrated in layers high in fine particles while iodine was not. Different affinity to particles between I and Cs leads to different environmental record.